Cybersecurity in Rural Hospitals: Reducing Attack Risks and Financial Losses - Hossain, Mohammad Ikbal; Ghosh, Dipak; Islam, Md Khairul; Auyon, MD Omum Siddique; Al Masud, Abdullah (Journal of Knowledge Management Practice, 2026)
This study investigates the cybersecurity vulnerabilities of rural hospitals, focusing on factors influencing both the frequency and financial consequences of cyberattacks. It examines how cybersecurity software, staff training, and investment levels affect attack rates and financial outcomes, while also considering the role of hospital size. Utilizing regression analysis, data were collected from 60 rural Bangladesh hospitals through institutional records, IT staff surveys, and public cybersecurity incident databases. Key variables included cybersecurity preparedness, training, investment, and hospital size. Hospitals with advanced cybersecurity software and well-trained staff reported fewer cyberattacks. Higher investment in cybersecurity significantly reduced the financial impact of breaches. Larger hospitals experienced more frequent attacks but were better equipped to manage associated costs. The findings highlight disparities in preparedness, with many rural hospitals lacking adequate resources. The study is limited to Bangladesh rural hospitals and relies on self-reported data, which may not fully capture the extent of cyber incidents. To mitigate cyber risks, rural hospitals should prioritize upgrading cybersecurity infrastructure and implementing comprehensive staff training. Policymakers should support these efforts through targeted funding and resources. This research addresses a critical gap in the literature by focusing on rural healthcare cybersecurity, offering a conceptual model for how software, training, and investment interact to shape cyber resilience and financial outcomes in resource-constrained environments.
Keywords: knowledge management; healthcare IT security; cyberattacks; cybersecurity investment; risk management